Symposium 5: Exploiting Distance Learning Methods and Multimedia-enhanced instructional content to support IT Curricula in Greek Technological Educational Institutes - Belsis, P.; Sgouropoulou, C.; Sfikas, K.; Pantziou, G.; Skourlas, C.; Varnas, J.; Alevizos, T.; Tsoukalas, V. (Proceedings of the International Conference on Networked Learning, 2008)
Various instructional strategies and material are at the disposal of the designers and tutors of online distance courses. However, in order to be effective, instructional interaction must exhibit some specific characteristics. Designers and tutors have to make (and change) decisions related to the selection and sequencing of the instructional material, specify when and how to cover students’needs during the phase of practicing specific skills and understand when to respond to students’difficulties about the subject matter. They also have to be aware (during the stages of the design of an online, distance-course) of the theory and practice already established in the context of distance tutoring. Standardization of expected learning outcomes in computer science departments has been acknowledged by internationally recognized organizations such as the ACM or the IEEE. According to the ACM/IEEE Computing curricula, "computer science students need to be able to develop conceptual and physical models, determine methods appropriate for providing efficient solutions to a given problem, and be able to select and implement appropriate solutions that reflect suitable constraints, including scalability and usability". The need for standardization and adoption of such principles has also emerged in the case of Greek Technological Education Institutes. Multimedia support also arises as an interesting challenge in modern academic education schemes. An overall support of these principles, as well as the description and evaluation of a multimedia enhanced teaching methodology has been part of our research considerations. An important constraint factor of Technological Education in Greece is the low ratio of the permanent teaching staff in respect to the continuously growing number of students. In addition, the ongoing explosive expansion of the Greek higher education has further aggravated the situation. Hence, the driving forces behind our efforts have been the need for standardization and co-operation, the limited time frame, and the lack of human teaching resources. Unfortunately, traditional instructional design models generally tend to be linear, step by step guides directing the tutor through a series of necessary stages. Therefore, an "ambitious", non-prescriptive, combined Content - Instruction and Tutor - Learner Centred Approach (COIN_TULE) must be applied. The suggested approach is based on activities and task sets emerging from published research results and practitioners’experience about the natures of learning, instruction and the subject matter. More precisely, we try to explore, examine and capture the relationship between Content and Instruction (COIN-relationship) and the relationship between Tutor and Learner (TULE-relationship). Such a work forms a basis for the extraction of useful characteristics that are incorporated into a methodological framework. The major advantage of this approach is that the Learner is put at the centre, which, not only improves understanding of the target audience, but also emphasises on the definition of course goals and learning objectives, the compilation of a detailed description of the content to be included, etc. In this paper we present a methodological framework for supporting the combinatory use of distance learning techniques, based on a mixed COIN_TULE and multimedia enhanced approach. At first, we briefly formulate the problem and describe the decisions which direct our choices. We explain the planning and design of our framework, presenting the sub-tasks related within the framework in more detail. Finally, we discuss evaluation of the learning experiments we have conducted, along with interesting outcomes and directions for future work.